Autosomal recessive primary microcephaly: an analysis of locus heterogeneity and phenotypic variation. Issue 10 (1st October 2002) - Roberts, E; Hampshire, D J; Pattison, L; Springell, K; Jafri, H; Corry, P; Mannon, J; Rashid, Y; Crow, Y; Bond, J; Woods, C G
Abstract : Background and objectives: Locus heterogeneity is well established in autosomal recessive primary microcephaly (MCPH) and to date five loci have been mapped. However, the relative contributions of these loci have not been assessed and genotype-phenotype correlations have not been investigated. Design: A study population of 56 consanguineous families resident in or originating from northern Pakistan was ascertained and assessed by the authors. A panel of microsatellite markers spanning each of the MCPH loci was designed, against which the families were genotyped. Results: The head circumference of the 131 affected subjects ranged from 4 to 14 SD below the mean, but there was little intrafamilial variation among affecteds (± 1 SD). MCPH5 was the most prevalent, with 24/56 families consistent with linkage; 2/56 families were compatible with linkage to MCPH1, 10/56 to MCPH2, 2/56 to MCPH3, none to MCPH4, and 18/56 did not segregate with any of the loci. Conclusions: MCPH5 is the most common locus in this population. On clinical grounds alone, the phenotype of families linked to each MCPH locus could not be distinguished. We have also shown that further MCPH loci await discovery with a number of families as yet unlinked.